New Bacillus thuringiensis strain isolated from the gut of Malabari goat is effective against Tetranychus macfarlanei. (13th May 2015) - Neethu, K. B.; Priji, P.; Unni, K. N.; Sajith, S.; Sreedevi, S.; Ramani, N.; Anitha, K.; Rosana, B.; Girish, M. B.; Benjamin, S.
Abstract: This study illustrates a novel strain (designated as BPU5) of Bacillus thuringiensis ( Bt ) isolated from the rumen of Malabari goat, capable of producing polymorphic δ ‐endotoxin crystals concomitantly with sporulation in Luria–Bertani medium (LB), and the δ ‐endotoxin was efficient to combat Tetranychus macfarlanei, a devastating mite. Polymorphic δ ‐endotoxin crystals produced were assessed by scanning electron microscopy and monitored its production concomitantly with sporulation in LB with or without sugar supplements. Toxicity of the δ ‐endotoxin was assessed on T. macfarlanei using leaf disc bioassay method. Mortality rate was determined by comparing the survival of mites on the diet (prepared in 10% sucrose and powdered rice husk) containing different concentrations (1–10 mg/ml) of 72‐h‐old crude pellet (dried mixture of δ ‐endotoxin (17 mg/g pellet), endospores and a few vegetative cells) or control diet with autoclaved pellet. The maximum production (1.39 mg/ml) of δ ‐endotoxin was observed at 72 h in LB. Among the sugars (glucose, sucrose, maltose or lactose) tested as additional carbon source, glucose (8 g/l) enhanced (1.82 mg/ml) the production of δ ‐endotoxin by 30%. The lethal concentration (LC50 ) required to kill 50% mites was estimated as 8.024 mg/ml. The δ ‐endotoxin produced by B. thuringiensis BPU5 is shown to efficiently combat T. macfarlanei, a devastating mite infesting agricultural fields.